GROWTH AND NUTRIENT UPTAKES OF YELLOW PASSION FRUIT (PASSIFLORA EDULIS VAR. FLAVICARPA) SEEDLINGS IN RESPONSE TO ORGANIC FERTILISER APPLICATION UNDER TROPICAL CONDITION: Passion fruit growth - JOSEPH-ADEKUNLE, Dr. Tunrayo Tinuoye; FAGBAYIDE, Julius Akinyemi; OLUBODE, Olusegun Olufemi (Journal of Agricultural Sciences (Belgrade), 2022)
Passionfruit is valued for its intense flavoured juice used as flavour in fruit juice mixes. Though cultivation is prominent in many tropical regions, it is a relatively new crop in southwest Nigeria though the ecology is conducive. Establishment of new crops rests on meeting the nutrients requirements. Two experiments were conducted at Abeokuta to evaluate optimum Sunshine Organic Fertilizer® (SOF) rate(s) required for seedlings growth. The SOF was applied at 0, 0.5, 1.0, 1.5, 2.0 and 2.5 t/ha in the experiments arranged in a Completely Randomized Design with three replicates. Application of SOF improved the growth of seedlings but above 2.0 t/ha resulted in depressed growth. In experiment 1, application at 0.5 t/ha SOF gave highest values of 152.7 cm, 19 mm and 19.0 for vine length, vine diameter and number of leaves. In experiment 2, the number of leaves was highest with 1.0 t/ha though similar to 1.5 and 2.0 t/ha. Application of SOF had significant influence on the seedling leaf area (LA) in both experiments and largest LA occurred in seedlings treated with SOF at 2.0 and 2.5 t/ha. The dry weight and foliar nutrient uptakes in both experiments were significantly influenced by SOF application. SOF at 0.5 t/ha in experiment 1 resulted in higher N uptake but reverse was the trend in experiment 2 with SOF at 1.5-2.5t/ha with higher nutrient uptakes. Conclusively the optimal rate of 2.0t/ha SOF had positive effects on the seedlings response.